The Me and My School Questionnaire: Examining the cross-cultural validity of a children's self-report mental health measure. Issue 1 (2nd January 2021) - Moffa, Kathryn; Wagle, Rhea; Dowdy, Erin; Palikara, Olympia; Castro, Susana; Dougherty, Danielle; Furlong, Michael J.
ABSTRACT: The Me and My School Questionnaire (M&MS) is a brief self-report measure of elementary school students' (ages 8–12) social, emotional, and behavioral challenges. As there is a need for brief self-report screening measures for students in elementary, or primary, school, this study examined the factor structure and measurement invariance of the M&MS for elementary school students in the United States (U.S.; N = 784) and the U.K. ( N = 538). Results replicated its two-factor structure (emotional difficulties and behavioral difficulties) with both samples. Convergent and discriminant validity, test–retest reliability, and measurement invariance for girls and boys were examined in the U.S. sample. Partial measurement invariance was established when comparing factor structures of the U.S. and U.K. samples. Implications for mental health monitoring, and for comparative international research are discussed.